Terracina - terra di briganti, tappa prediletta dai (grand-)turisti - Arts, Clemens (Incontri. Rivista europea di studi italiani, 2012)
Terracina: bandit territory and resort cherished by (grand-) touristsFor travellers who left the Eternal City, Terracina was one of the first stages, and almost an obligatory one, on their way to Naples and further south. The charming fishing town on the Tyrrhenian Sea situated on the Via Appia offered to those who had crossed the boring and bothersome Pontine Marshes a glimpse of the lushest Mediterranean vegetation and views. Yet another aspect of Terracina’s historical background is the protracted terrifying presence of notorious bandits such as Fra Diavolo and Gasbarrone.This article questions the imagological implications of these mytho-cultural assets of Terracina in literature, with a focus on ‘Romantic’ early Nineteen Century travel literature at large (Irving Washington, Stendhal), in which the point of view is mostly from a visitor's perspective, whereas authoritative studies, e.g. by Eric Hobsbawm, have rightly stressed the crucial importance of the insiders’ point of view as well.As an excursus from this cultural and historical context Pier Paolo Pasolini’s delicious ‘Terracina’ comes in to offer just such an insider’s point of view, telling the story of two Roman ‘ragazzi di vita’ – or ‘briganti’, as the villagers call them – who become tourists themselves and get fatally attracted by the idyllic Terracina seascape.